Application of microCT to the non-destructive testing of an additive manufactured titanium component - du Plessis, Anton; le Roux, Stephan G.; Els, Johan; Booysen, Gerrie; Blaine, Deborah C. (Case studies in nondestructive testing and evaluation, 2015)
In this paper the application of X-ray microCT to the non-destructive testing of an additive manufactured titanium alloy component of complex geometry is demonstrated. Additive manufacturing of metal components is fast growing and shows great promise, yet these parts may contain defects which affect mechanical properties of the components. In this work a layered form of defect is found by microCT, which would have been very difficult or impossible to detect by other non-destructive testing methods due to the object complexity, defect size and shape and because the pores are entirely contained inside the object and not connected to the surface. Additionally, this test part was subjected to hot isostatic pressing (HIPPING) and subsequently scanned. Comparing before and after scans by alignment of the volumes allows visualization and quantification of the pore size changes. The application of X-ray microCT to additive manufacturing is thus demonstrated in this example to be an ideal combination, especially for process improvements and for high value components.